COLD WAX BATIK TRAINING IN IMPROVING STUDENTS' SKILLS - yanti, fitri (EDUCATE, 2024)
Batik is a decorative design made using wax as a color blocking material, so that the dye will not come into contact with the part of the fabric covered in wax during dyeing. In general, the process of making batik uses a tool in the form of a canting. With the new batik innovation, cold nights can be used as an alternative to make the batik making process easier and faster. In the textile science course, students learn how to dye fabric. One way to understand the coloring process is to do cold night batik training. The results of the cold night batik training are so that students can improve their batik skills.